The Future Ready Ideas Lab: Future Proofing Bioscience Students Enterprise Skills - Barrow, John; Perkins, Joy; Marini, Pietro; Davidson, Ann (Compass: Journal of Learning and Teaching in Higher Education, 2020)
Given the pace of technological change, today’s students need to be prepared for changing employment roles in an ever-evolving world. Increasingly, employers require graduates to be innovative, adaptable and resilient, and have an enterprising mind-set. Enterprise education supports students to develop these key attributes and skills, enabling them to engage with the pace of change. In our teaching context the challenges of delivering enterprise education is to support and engage 300 students, at an early stage in their life sciences degree programme, to start developing core enterprising behaviours. To address this, a bespoke enterprise workshop was devised. A Kirkpatrick evaluation-based survey was then used to investigate the following themes: 1) students’ satisfaction and reaction to the enterprise session; 2) students’ ability to articulate their skills; 3) participants’ behaviour post-session and 4) benefits derived from the session. The data collected reveals students’ awareness of their skills and their understanding of what may be required of future employers and their employees. Although it is also clear from the data, broadening all students’ horizons and their enterprise engagement is challenging. The next step is to conduct a longitudinal study to gather a time perspective view on this cohort’s enterprise knowledge and learning.